The Effects of Social Media Advertising on Social Search in China: Evidence from Luxury Brand - GAO, XING; Kim, Sang Yong; Kim, Da Yeon; Lee, Seung Min (ASIA MARKETING JOURNAL, 2019)
This study examines the relationship between social media advertisement and customer interest in the context of luxury brands. Further, this study investigates the effective ways to utilize visual types (pictorial advertisement and video advertisement) and contents types (website link and hash-tag) in social media advertising by proposing a time-series model to estimate the long-term effect of social media advertising on social search. We find that the pictorial advertisements are more effective than video advertisements, which provides a different result from previous existing research. In addition, advertisements using hashtags are more effective than web links due to efficiency of the search feature. Finally, since the number of brand fans also have a positive effect on advertising interest, it is essential to utilize social media advertising for the enhancement of customers’ interests. Confirming that the effectiveness of social media advertising varies depending on how the visual contents and text are presented, this research can help marketing managers to assess predicted outcomes of using various methods of social media advertising.